The Production Of Flavonoids (Quercetin And Hesperetin) From Callus Culture Of Citrus Aurantifolia (Christm & Panzer) Swingle - Siti Mahyuni, (1999)

(untitled)
The application of plant tissue culture technique for plant flavonoids production shows some promising results. However, certain limitation exist mainly because many cultures do not produce significant amount of the characteristic compounds from the plants which they were derived. Thus, the objectives of this study were to establish the C. aurantifolia (Christm & Panzer) Swingle callus cultures for bioproduction system of flavonoid compounds (quercetin and hesperetin) and to optimize their production by application of yeast extract supplementation. The callus culture was established by planting the explant excised from peel of mature fruit on the basal medium Murashige and Skoog (MS) (1 962) supplemented with 1.5 mg/L (w/v) (X-naphthalene acetic acid (NAA),